The Effect of Macroeconomics on the Receipt of Zakat, Infaq, and Shadaqah at BAZNAS Central for 2015-2024 Period - Juliarty, Noer Resky; Fitri, Resfa; Achsani, Muhammad Nur Faaiz Fathah; Beik, Irfan Syauqi (International Journal of Zakat, 2025)
In recent years, Indonesia's economy has grown steadily, supported by strong household purchasing power and stable investment. However, this stability was disrupted with the emergence of the COVID-19 pandemic in early 2020. This study aims to analyze the effect of macroeconomic variables on the collection of zakat, infaq, and sadaqah at BAZNAS Central during the 2015–2024 period. The research use secondary quarterly time-series data from 2015 to 2024. The analysis is conducted using descriptive analysis combined with the Autoregressive Distributed Lag (ARDL) method. The results show more clearly that GDP consistently exerts a positive and significant influence on zakat as well as infaq and shadaqah receipts in both the short and long run, confirming the central role of economic growth in strengthening Islamic philanthropic capacity. Meanwhile, the Consumer Price Index (CPI), as a proxy for inflation, and the BI Rate were not proven to significantly affect infaq and shadaqah receipts; however, CPI demonstrates a positive long-run effect on zakat, and the BI Rate shows a negative but weak influence, indicating limited monetary policy transmission to ZIS behavior. The impact of the COVID-19 pandemic was found to be significantly negative for zakat receipts, but relatively insignificant for infaq and shadaqah. Furthermore, digitalization at BAZNAS is shown to significantly increase ZIS collection, underscoring the growing role of technological adoption in expanding accessibility and strengthening fundraising performance. Overall, these findings highlight the need for macroeconomic stability and continuous digital transformation to optimize ZIS mobilization.